2013
DOI: 10.2967/jnumed.112.110890
|View full text |Cite
|
Sign up to set email alerts
|

International Validation Study for Interim PET in ABVD-Treated, Advanced-Stage Hodgkin Lymphoma: Interpretation Criteria and Concordance Rate Among Reviewers

Abstract: At present, there are no standard criteria that have been validated for interim PET reporting in lymphoma. In 2009, an international workshop attended by hematologists and nuclear medicine experts in Deauville, France, proposed to develop simple and reproducible rules for interim PET reporting in lymphoma. Accordingly, an international validation study was undertaken with the primary aim of validating the prognostic role of interim PET using the Deauville 5-point score to evaluate images and with the secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
157
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 274 publications
(181 citation statements)
references
References 18 publications
17
157
2
5
Order By: Relevance
“…This categorization has a high interobserver agreement in HL and DLBCL. 5,6 However, FDG-PET is also a quantitative imaging technique, allowing semi-quantitative imaging interpretation, using standardized uptake values (SUV). Reporting change of FDG uptake (usually expressed as a relative change) can also be used for interim response assessment.…”
Section: Assessment Of Interim-pet Scansmentioning
confidence: 99%
“…This categorization has a high interobserver agreement in HL and DLBCL. 5,6 However, FDG-PET is also a quantitative imaging technique, allowing semi-quantitative imaging interpretation, using standardized uptake values (SUV). Reporting change of FDG uptake (usually expressed as a relative change) can also be used for interim response assessment.…”
Section: Assessment Of Interim-pet Scansmentioning
confidence: 99%
“…12,21 In the current study, we applied a Deauville score based on PET/CT to assess tumor response, because it has been reported to be feasible and reproducible, with good interobserver agreement. 22 So far consensus has not been achieved on the positive and negative thresholds of Deauville five-point scale, recent studies have suggested the prognostic value of negative PET/CT response (DS 1-3) before ASCT for significant PFS and OS in patients with diffuse large B-cell lymphoma and follicular lymphoma. 23,24 In addition, for ENKTL patients, Khong et al 25 found that mid-treatment DS of 1-3 was a significant independent predictor of OS and PFS with 2-year OS and PFS rate of 81% and 62%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also took into account mixed-cellularity or lymphocyte-depleted histologies, the presence of B symptoms or high erythrocyte sedimentation rate, and bulky disease as adverse prognostic factors [4,5]. Moreover, disease extensions measured by Computed Tomography (CT), and early response to treatment measured by Positron Emission Tomography (PET) have demonstrated a powerful prognostic ability [6,7].…”
Section: Purposementioning
confidence: 99%